THE IMPACT OF TAX AUDITS AND TAX ARREARS COLLECTION ON TAX REVENUE: A CASE STUDY AT KPP PRATAMA KEDIRI - Putri, Chintya Cholivah Eka; Rahayu, Puji; Niam, Muhammad Alfa (Accounting Studies and Tax Journal (COUNT), 2025)
This study investigates the effect of tax audit implementation and tax arrears collection on tax revenue at KPP Pratama Kediri, Indonesia. The research is grounded in the ongoing challenge of improving tax compliance and revenue collection in a self-assessment tax system. Employing a quantitative research design, data were collected through questionnaires distributed to 90 business taxpayers selected using purposive sampling. Statistical analyses, including multiple linear regression, were applied to examine the relationships. The findings reveal that both tax audits and tax arrears collection significantly and positively affect tax revenue, both individually and simultaneously. The implications suggest that enhancing the effectiveness of audit and collection mechanisms can significantly contribute to national tax revenue goals. This study contributes to the existing literature by validating the instrumental role of tax enforcement strategies in the Indonesian context.